Radiative Thermal and Solutal Stratification Effects on Magnetized Dissipative Second-Grade Nanofluid Flow over an Exponentially Stretching Sheet - Deepika, A. R.; Govardhan, K.; Rafiuddin, M.; Reddy, G. Janardhana; Basha, Hussain (Discontinuity, Nonlinearity, and Complexity, 2026)
Present numerical analysis describes the impact of thermal and solutal stratifications on the boundary layer flow of magnetized second-grade fluid over an exponentially stretching sheet under the influence of viscous dissipation and porous medium effects. The doubly stratified porous medium comprised with a stretchable sheet of the form U_w(x)= U_oe^x/L and designated along the axial flow direction with T_w(x)= T_o+be^x/2L and C_w(x)= T_o+ae^x/2L is the thermal and concentration fields at the surface. Based on the flow geometry, the current physical situation yields the complex nonlinear system of differential equations and which are not amenable to any of the direct methods. Hence, a robust Runge-Kutta 4^th order method is implemented to solve the representative system of flow equations. The outcomes of the current investigation are presented for various values of physical parameters in the boundary layer regime adjacent to the stretching sheet in the form of velocity, thermal and concentration profiles. Momentum boundary layer thickens and thermal profile significantly suppressed for the enhancing values of second-grade fluid parameter. Adjacent to the stretching sheet, the velocity field considerably diminished for the rising values of magnetic number. Magnifying Brownian motion parameter suppressed the concentration field, whereas increasing thermophoresis parameter enhances the concentration field. Thermal and concentration fields significantly decayed for the increasing values of thermal and solutal stratification numbers. However, the similarity solutions presented in this investigation excellently matching with the former results in the literature and this fact assures the validity of the current solutions.